Urocystis piptatheri sp. nov. (Urocystaceae), a new species of smut fungus on Piptatherum laterale (Poaceae) from Pakistan - Afshan, Najam-Ul-Sahar; Anwar, Ayesha; Riaz, Maria; Din, Siraj Ud; Khalid, Abdul Nasir (Phytotaxa, 2020)
A new species of smut fungi, Urocystis piptatheri is described from Kumrat Valley, Pakistan based on morphological characters and molecular phylogenetic analysis of nuclear ribosomal DNA comprising the internal transcribed spacer (ITS) regions along with large subunit (LSU). The new species is characterized by the large size of its spore balls, size and number of central spores, spore wall thickness, sori in leaves and by the host plant species (Piptatherum laterale). Phylogenetic analysis of nuclear ribosomal ITS and LSU nucleotide sequences confirmed the novelty of Urocystis piptatheri. A key for the identification of Urocystis species on Pipthatherum spp. is provided.